Migrating legacy Web applications - Cajas, Viviana (2021)
Since the adoption of portable devices like smartphones or smartwatches, the usage of applications has rapidly increased for supporting diverse daily activities from connecting with friends to measuring running distance. Since the Apps are an ubiquitous tool in everyday life, it is also an opportunity for a new digital business model. However, there are legacy applications implementing the core business process and rules that are not designed to run properly on new mobile devices. The migration of legacy applications by developing a new version from scratch introduces risk and uncertainty. This study proposes an approach to assist the migration of legacy Apps so that available functionality is prioritized, the experience of User Interface is re-thought, and the new design is evaluated with a preliminary running version of the legacy app. The proposed method is based on a Markov chain model. An experiment on ten participants shows that a dynamic user interface that implements the Markov model provides the users with a better usability. This work suggests that the heuristics make possible a smart and proactive interface design